Optimalisasi Pengelolaan Limbah Plastik melalui Pemanfaatan Mesin Pres Sampah untuk Efisiensi Penyimpanan dan Distribusi - Arie Noor Rakhman; Fajar Yulianto Prabowo; Fivry Wellda Maulana; Jarwanto Jarwanto (JPM: Jurnal Pengabdian Masyarakat, 2026)
Community-based plastic waste management continues to face challenges related to the large volume of recyclable materials, resulting in inefficient storage, distribution, and logistics management. These conditions reduce operational effectiveness and limit the economic benefits obtained by waste bank managers. This community service program aimed to enhance the capacity of the Wimalandaru Waste Bank managers through the transfer of waste compactor technology and technical assistance for its application in plastic waste management. The program employed a participatory approach based on the Participatory Action Learning System (PALS), consisting of initial condition assessment, technology implementation, operational training and socialization, technical mentoring, and monitoring and evaluation activities. The results showed that the managers were able to independently operate the waste compactor, apply occupational safety procedures, and manage the plastic compaction process more effectively. The implementation of the compactor transformed plastic gallons and bottles into compact cubic blocks, improving storage and transportation efficiency. The technology contributed to a reduction in logistics costs by 96.65% for plastic gallons and 93.33% for plastic bottles, resulting in substantial improvements in operational efficiency. Furthermore, the mentoring activities enhanced both the technical and managerial capacities of the managers in equipment operation, logistics management, storage arrangement, and equipment maintenance. The program demonstrates that technology transfer combined with continuous mentoring can improve operational efficiency, strengthen the institutional capacity of community-based waste banks, and support more effective, safer, and sustainable plastic waste management practices.